The Meaning and Implications of Multicultural Education for Children in Indonesia - Mahariah; Vika Yuliana Putri; Muhammad Fathurrahman; Nadia Salsabila (Journal of Contemporary Gender and Child Studies, 2023)
From the perspective of the Indonesian people, multicultural education is not something surprising, because the character and personality of the Indonesian people themselves are accustomed to the extraordinary diversity of the archipelago. Multicultural education is an alternative for integrating the diversity that exists in Indonesia. Because of this, the aim of this research is to examine in more depth the meaning and implications of multicultural education in Indonesia. And the method used in this research is literary study or library research, namely by collecting information from various sources, both taken from books and journals related to the research problem. The results of this research show that multicultural education is an educational strategy that is applied in all subjects by using the cultural differences that exist in students such as differences in religion, race, ethnicity, and so on, and the implications of this multicultural education are multicultural education. It will form students who can appreciate cultural diversity, recognize cultural diversity, and by utilizing this cultural diversity to foster multicultural awareness within the frame of "Bhinneka Tunggal Ika".